A Systematic Review Approach to Find Robust Items of the Zimbardo Time Perspective Inventory - Peng, Chunhua; Yue, Caizhen; Avitt, Andrew; Chen, Youguo (Frontiers in Psychology, 2021)
Zimbardo Time Perspective Inventory (ZTPI) is one of the most well-known and widely used measures of time perspective. Various short versions were proposed to resolve the psychometric problems of the ZTPI. The present study conducted a systematic review to obtain 25 short versions, calculate the frequency of each item of the ZTPI in short versions, and hypothesized that the more frequent the item, the more robust it is. The hypothesis was tested by assessing the structural validity and internal consistency of short forms with high, medium, and low frequent items in Chinese samples (575 children, 407 undergraduates, and 411 older adults). Structural validity and internal consistency analyses showed that the form with more frequent items had better psychometric properties; Item frequencies were positively correlated with factor loadings. The results suggest that the systematic review is an effective approach to identify the robust items of the ZTPI. This approach is general and can be the basis to improve the psychometric properties of scales in social science.